A Multicenter Randomized Trial to Evaluate a Chemical‐first or Electrical‐first Cardioversion Strategy for Patients With Uncomplicated Acute Atrial Fibrillation. (19th August 2019) - Scheuermeyer, Frank X.; Andolfatto, Gary; Christenson, Jim; Villa‐Roel, Cristina; Rowe, Brian
Abstract: Background: Emergency department (ED) patients with uncomplicated atrial fibrillation (AF) of less than 48 hours may be safely managed with rhythm control. Although both chemical‐first and electrical‐first strategies have been advocated, there are no comparative effectiveness data to guide clinicians. Methods: At six urban Canadian centers, ED patients ages 18 to 75 with uncomplicated symptomatic AF of less than 48 hours and CHADS2 score of 0 or 1 were randomized using concealed allocation in a 1:1 ratio to one of the following strategies: 1) chemical cardioversion with procainamide infusion, followed by electrical countershock if unsuccessful; or 2) electrical cardioversion, followed by procainamide infusion if unsuccessful. The primary outcome was the proportion of patients discharged within 4 hours of arrival. Secondary outcomes included ED length‐of‐stay (LOS); prespecified ED‐based adverse events; and 30‐day ED revisits, hospitalizations, strokes, deaths, and quality of life (QoL). Results: Eighty‐four patients were analyzed: 41 in the chemical‐first group and 43 in the electrical‐first group. Groups were balanced in terms of age, sex, vital signs, and CHADS2 scores. All patients were discharged home, with 83 (99%) in sinus rhythm. In the chemical‐first group, 13 of 41 patients (32%) were discharged within 4 hours compared to 29 of 43 patients (67%) in the electrical‐first group (p = 0.001). In the chemical‐first group, the median ED LOS was 5.1 hours (interquartile range [IQR] = 3.5 to 5.9 hours) compared to 3.5 hours (IQR = 2.4 to 4.6 hours) in the electrical‐first group, for a median difference of 1.2 hours (95% confidence interval = 0.4 to 2.0 hours, p < 0.001). No patients experienced stroke or death. All other outcomes, including adverse events, ED revisits, and QoL, were similar. Conclusion: In uncomplicated ED AF patients managed with rhythm control, chemical‐first and electrical‐first strategies both appear to be successful and well tolerated; however, an electrical‐first strategy results in a significantly shorter ED LOS.